The Rationality of Official Intervention in the Forward Exchange Market: Further Comment - Ward, Richard (Quarterly Journal of Economics, 1965)
Journal Article The Rationality of Official Intervention in the Forward Exchange Market: Further Comment Get access Richard Ward Richard Ward University of Southern California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 79, Issue 1, February 1965, Pages 148–150, https://doi.org/10.2307/1880519 Published: 01 February 1965